On the current flow mechanism in the Au-TiBx-n-GaN-i-Al₂O₃ Schottky barrier diodes - Belyaev, A.E.; Boltovets, N.S.; Ivanov, V.N.; Klad’ko, V.P.; Konakova, R.V.; Kudryk, Ya.Ya.; Kuchuk, A.V.; Milenin, V.V.; Sveshnikov, Yu.N.; Sheremet, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
We investigated a current flow mechanism in the Au−TiBx−n-GaN−i-Al₂O₃ Schottky barrier diodes, in which the space-charge region width is much over the de Broglie wavelength in GaN. An analysis of the temperature dependences of the I−V curves of forward-biased Schottky barriers showed that, in the temperature range 80−380 K, the current flow occurs as a tunneling one along dislocations crossing the space-charge region. The dislocation density ρ estimated from the I−V curves (in accordance with the model of tunneling along the dislocation line) was ≈ 1.7×10⁷ cm⁻². This value is close to that obtained with x-ray diffraction technique